2012
DOI: 10.1002/jtr.1907
|View full text |Cite
|
Sign up to set email alerts
|

Do Tourism Receipts Contribute to the Sustainability of Current Account Deficits: a Case Study of Barbados

Abstract: Given Barbados’ recent history of persistent current account deficits and reliance on tourism as a major source of foreign exchange and driver of the economy, this paper investigated the contribution of tourism receipts to the sustainability of Barbados’ current account deficits. Utilizing an inter‐temporal budget approach, it was found that Barbados’ current account deficits were weakly sustainable as a result of tourism's contribution, underscoring the island's dependence on the industry. Copyright © 2012 Jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…Recently, there are a growing number of sources in literature about this causality, mostly in developing countries (Caldereon et al, 2002;Konan and Maskus, 2016). Lorde et al (2010) examined the case of Barbados, fi nding a positive impact. A positive relationships between tourism and growth and tourism contribution to balance of payment income has also been found for Turkey (Cetinas and Bektas, 2008;Arslantuk and Atan, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recently, there are a growing number of sources in literature about this causality, mostly in developing countries (Caldereon et al, 2002;Konan and Maskus, 2016). Lorde et al (2010) examined the case of Barbados, fi nding a positive impact. A positive relationships between tourism and growth and tourism contribution to balance of payment income has also been found for Turkey (Cetinas and Bektas, 2008;Arslantuk and Atan, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, tourism has emerged as the main source of foreign exchange, accounting for nearly 50% of foreign earnings on average. Further, current account deficits in Barbados would be unsustainable without the earnings from tourism (Lorde, Lowe, & Francis, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The explanation lies in the fact that tourism is a significant export driver in Croatia (Pavlic, Svilokos, & Tolic, 2015) and tourism exports can hardly be linked to imports. Similarly and based on the same inter-temporal budget approach, Lorde et al (2013) found that Barbados' current account deficits were weakly sustainable as a result of tourism's contribution and pointed out the island's dependence Table 2. Estimation results (state-space model with T.V.P) for the sustainability of international tradethe case of Serbia.…”
Section: Research Results and Discussionmentioning
confidence: 91%